Scoping review identifies significant number of knowledge translation theories, models, and frameworks with limited use - Strifler, Lisa; Cardoso, Roberta; McGowan, Jessie; Cogo, Elise; Nincic, Vera; Khan, Paul A.; Scott, Alistair; Ghassemi, Marco; MacDonald, Heather; Lai, Yonda; Treister, Victoria; Tricco, Andrea C.; et al. (Journal of clinical epidemiology, 2018)
To conduct a scoping review of knowledge translation (KT) theories, models, and frameworks that have been used to guide dissemination or implementation of evidence-based interventions targeted to prevention and/or management of cancer or other chronic diseases. We used a comprehensive multistage search process from 2000 to 2016, which included traditional bibliographic database searching, searching using names of theories, models and frameworks, and cited reference searching. Two reviewers independently screened the literature and abstracted the data. We found 596 studies reporting on the use of 159 KT theories, models, or frameworks. A majority (87%) of the identified theories, models, or frameworks were used in five or fewer studies, with 60% used once. The theories, models, and frameworks were most commonly used to inform planning/design, implementation and evaluation activities, and least commonly used to inform dissemination and sustainability/scalability activities. Twenty-six were used across the full implementation spectrum (from planning/design to sustainability/scalability) either within or across studies. All were used for at least individual-level behavior change, whereas 48% were used for organization-level, 33% for community-level, and 17% for system-level change. We found a significant number of KT theories, models, and frameworks with a limited evidence base describing their use.